ANALISIS PENYALAHGUNAAN RHODAMIN B PADA KERUPUK BERWARNA MERAH YANG BEREDAR DI PASAR KOTA BENGKULU DENGAN MENGGUNKAN METODE KLT DAN SPEKTROFOTOMETRI UV-Vis - Adellia Giyani Putri; Mulia, Putri; Ikhsan; Slamet, Samwilson; Perma Sari, Rose Intan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rhodamine B is a synthetic dye that is banned in food products because it can cause health problems, such as irritation, liver damage, and potential carcinogenicity. However, Rhodamine B is still being misused in various types of food, particularly red crackers sold on the market. This study aims to investigate the misuse of Rhodamine B and determine its levels in red crackers sold at Bengkulu City Market. The methods used were Thin-Layer Chromatography (TLC) for qualitative analysis and UV-Vis Spectrophotometry for quantitative analysis. A total of 15 samples of red crackers were collected from several markets in Bengkulu City using purposive sampling. The identification results using TLC showed that 4 out of 15 samples tested positive for Rhodamine B, namely samples PM5, PP1, PK3, and PK5. This was indicated by Rf values close to the Rhodamine B standard as well as the appearance of yellow-orange fluorescence when examined under UV light at 254 nm and 365 nm. Quantitative analysis conducted via UV-Vis spectrophotometry at a maximum wavelength of 542.95 nm revealed Rhodamine B concentrations of 0.0036% for sample PM5, 0.0066% for sample PP1, 0.0037% for sample PK3, and 0.0078% for sample PK5. Based on the research findings, it can be concluded that Rhodamine B is still being misused in red crackers sold at Bengkulu City Market, meaning that these products do not meet food safety standards.